2019
DOI: 10.1155/2019/9535070
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of a Growing Rod with Sliding Pedicle Screw System for Early-Onset Scoliosis

Abstract: Early-onset scoliosis (EOS) remains a challenging condition for which current nonfusion surgeries require iterative lengthening surgeries. A growing rod with sliding pedicle screw system (GRSPSS) was developed to treat spinal deformities without repeated operative lengthening. This study was performed to evaluate whether GRSPSS had similar stability as a conventional pedicle screw system to maintain deformity correction. A serial-linkage robotic manipulator with a six-axis load cell positioned on the end-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In a study by Ouyand et al, the stability of the sliding growing rod technique was evaluated on sheep spine, the technique protected the stability as much as a totally xated system also in movements like exion, extension, and lateral bending along with posterior instrumentation and fusion performance. In the literature, the outcomes of sliding growing double rod technique is more successful with less complication rates when compared to the single growing rod system in patients with early onset scoliosis and congenital scoliosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ouyand et al, the stability of the sliding growing rod technique was evaluated on sheep spine, the technique protected the stability as much as a totally xated system also in movements like exion, extension, and lateral bending along with posterior instrumentation and fusion performance. In the literature, the outcomes of sliding growing double rod technique is more successful with less complication rates when compared to the single growing rod system in patients with early onset scoliosis and congenital scoliosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…From a physical perspective, the sagittal and coronal planes can be controlled by segmental screws with rigid rods; however, only fixed orthogonal devices prevent rod rotation. 23,24 In a short-segment fusion study, Peltier et al showed that constructs with one cross-link were 31% stiffer and those with 2 cross-links were 43% stiffer in torsion compared with constructs without cross-links. 9 In our results, axial stiffness was significantly higher in Group D than Group C, and similar results were observed between Groups D and E. Our results demonstrated that in a long-segment spinal construct, greater rotational rigidity may be achieved in a position-dependent manner by increasing the separation distance for the 2 crosslink configuration (Group C compared with Group D).…”
Section: Discussionmentioning
confidence: 99%
“…From a physical perspective, the sagittal and coronal planes can be controlled by segmental screws with rigid rods; however, only fixed orthogonal devices prevent rod rotation. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Ouyang et al compared this technique with a posteriorly fused sheep spine to evaluate the stability of the SGR technique in a study conducted in sheep spine. These researchers showed that the SGR technique has stability with respect to flexion, extension, and lateral bending movements in addition to the performance of posterior instrumentation and fusion to the spine [ 20 ].…”
Section: Discussionmentioning
confidence: 99%